2021
DOI: 10.1108/jcre-06-2020-0027
|View full text |Cite
|
Sign up to set email alerts
|

Occupants’ satisfaction and perceived productivity in open-plan offices designed to support activity-based working: findings from different industry sectors

Abstract: Purpose In the rise of offices designed to support activity-based working (ABW), parts of industry have fully transitioned to open-plan environments and then later to unassigned seating, whereas other parts, such as tertiary education, are still in the process of moving away from individual offices. There are a few relevant studies to understand how occupants from industry sectors with different levels of adoption of ABW perceived environments designed to support this way of working. This paper aims to contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…From the physical environment perspective, the well-known challenges around open plan working, including lack of control over the physical environment (Candido et al , 2020; Ekstrand and Damman, 2016; Candido et al , 2021), lack of visual and acoustics privacy (Brand and Smith, 2005; Bodin Danielsson and Bodin, 2009), lack of ability to perform focused work and being interrupted (Candido et al , 2019), wherein the spotlight again. The initial impression is that some of these issues were “resolved” by having people working from home with some reporting productive outcomes arising from the ability to concentrate alone (Parker, 2020).…”
Section: Physical Environmentmentioning
confidence: 99%
“…From the physical environment perspective, the well-known challenges around open plan working, including lack of control over the physical environment (Candido et al , 2020; Ekstrand and Damman, 2016; Candido et al , 2021), lack of visual and acoustics privacy (Brand and Smith, 2005; Bodin Danielsson and Bodin, 2009), lack of ability to perform focused work and being interrupted (Candido et al , 2019), wherein the spotlight again. The initial impression is that some of these issues were “resolved” by having people working from home with some reporting productive outcomes arising from the ability to concentrate alone (Parker, 2020).…”
Section: Physical Environmentmentioning
confidence: 99%
“…This null finding might be due to several psychological mechanisms activated when transitioning to an A-FO. On the one hand, the feeling of decreased privacy (Brunia et al, 2016; Candido et al, 2021; Gorgievski et al, 2010) might lead to more robust withdrawal behavior. On the other hand, in the seventies, Altman (1975) suggested that autonomy, or the ability to control or regulate to maintain self-identity, would be a function of privacy.…”
Section: Discussionmentioning
confidence: 99%
“…Open-plan offices are inherently susceptible to the spread of COVID-19 among coworkers [35], with some writers predicting the end of this concept [114,115] given underlying pre-pandemic concerns of workplace confidentiality and productivity in open plan designs [116,117]. Assuming that the concept will not fade away given perceptions by management for the need of command-and-control staff management, and a lack of opportunities for the ready modifications to internal structures [118,119], consideration needs to be given to the design of ventilation. As most activity in open plan offices is sedentary, with most staff working on workstations, speaking on the phone or via videoconferencing, air should be downwards extracted either at the desk level (akin to the ventilation in nail salons) or at the intersections and nodes of desk arrays, rather than continuing the current pattern of air dispersion through the entire space (Figure 5).…”
Section: Officesmentioning
confidence: 99%